The nature of animal crime - Buchfield, Keri B. (Crime & delinquency, 2018)
This study sought to contribute to our sociological understanding of animal crime. Using Chicago Police Department data that include primary and secondary charges of all animal crimes between 2009 and 2012, findings indicate that most animal crime offenders were male, African American or Hispanic, and under 35 years. When other crimes were committed with animal crime, they were likely drug or weapons offenses. Juveniles arrested for animal crimes tended to commit more severe animal crimes than adult offenders. Finally, regression results indicated that race was positively related to animal crime severity, while concurrent drug offenses were inversely related to animal crime severity. Implications for theory, research, and policy are discussed.